Diseño de una máquina de termoformado multifuncional didáctica para el laboratorio de procesos en la Fundación Universidad de América (2021)
This document presents the development of the design of a multifunctional thermoforming machine, which was proposed as an alternative to be implemented in the laboratories of the Universidad de América Foundation, in order to provide support in the teaching and learning of the manufacturing processes with the polymers. For this, a machine proposal is proposed that will carry with it the three thermoforming methods, thus proposing different types of alternatives to the systems and subsystems that make up the machine, selecting the best alternative based on criteria and requirements through a decision matrix and prioritization which facilitates and provides a better selection of alternatives; performing the corresponding calculations for them.